Transcriptome Analysis Reveals Key Genes Involved in the Response of Triticum urartu to Boron Toxicity Stress - Gul Sema Uyar; Anamika Pandey; Mehmet Hamurcu; Tomas Vyhnanek; Mustafa Harmankaya; Ali Topal; Sait Gezgin; Mohd. Kamran Khan (Agronomy)
The domestication and breeding of wheat genotypes through the years has led to the loss in their genetic variation, making them more prone to different abiotic stresses. Boron (B) toxicity is one of the stresses decreasing the wheat cultivars’ yield in arid and semi-arid regions around the world. Wild wheat progenitors, such as Triticum urartu Thumanian ex Gandilyan, possess a broader gene pool that harbors several genes conferring tolerance to various biotic and abiotic stresses. Unfortunately, T. urartu is not well-explored at the molecular level for its tolerance towards B toxicity in soil. In this study, for the first time, we compared the transcriptomic changes in the leaves of a high B-tolerant T. urartu genotype, PI662222, grown in highly toxic B (10 mM B in the form of boric acid) with the ones grown in the control (3.1 μM B) treatment in hydroponic conditions. The obtained results suggest that several mechanisms are involved in regulating the response of the studied T. urartu genotype toward B toxicity. All the growth parameters of T. urartu genotype, including root–shoot length, root fresh weight, and root–shoot dry weight, were less affected by high boron (10 mM) as compared to the boron-tolerant bread wheat cultivar. With a significant differential expression of 654 genes, 441 and 213 genes of T. urartu genotype were down- and upregulated, respectively, in the PI662222 leaves in high B in comparison to the control treatment. While key upregulated genes included those encoding RNA polymerase beta subunit (chloroplast), ATP synthase subunit gamma, chloroplastic, 60S ribosomal protein, and RNA-binding protein 12-like, the main downregulated genes included those encoding photosystem II protein D, ribulose bisphosphate carboxylase small subunit, and peroxidase 2-like. Interestingly, both Gene Ontology enrichment and KEGG pathways emphasized the possible involvement of the genes related to the photosynthetic process and apparatus in the high B tolerance of the T. urartu genotype. The further functional characterization of the identified potential T. urartu genes will facilitate their utilization in crop improvement programs for B toxicity stress.